1999 Proceedings. 49th Electronic Components and Technology Conference (Cat. No.99CH36299)
DOI: 10.1109/ectc.1999.776162
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life prediction of flip-chips in terms of nonlinear behavior of solder and underfill

Abstract: The nonlinear properties of eutectic solder and underfill FP4526 have been reported and incorporated into ABAQUS material model library for the fatigue life prediction of advanced electronic packages. The methods of unified constitutive modeling, separated Constitutive modeling, and fatigue life prediction have been described and compared in details. The nonlinear constitutive modeliig of solder alloys and underfills plays an important role in the life prediction in terms of the correct calculation of inelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Solder joints' fatigue life in thermal cycling tests has been studied for decades using the finite element method. While many researchers are investigating the influence of thermal cycling on the reliability, it is still a heating-concerned problem to be discussed [4][5][6][7][8]. Xuejun Fan [9] found that the ramp rate, the dwell time, and the frequency of thermal cycling have a great impact on the reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Solder joints' fatigue life in thermal cycling tests has been studied for decades using the finite element method. While many researchers are investigating the influence of thermal cycling on the reliability, it is still a heating-concerned problem to be discussed [4][5][6][7][8]. Xuejun Fan [9] found that the ramp rate, the dwell time, and the frequency of thermal cycling have a great impact on the reliability.…”
Section: Introductionmentioning
confidence: 99%